Not all trade restrictions are created equally - Matthew T. Cole (University College Dublin, UCD School of Economics, 2010)
There has been great focus in the recent trade theory literature on the introduction of firm heterogeneity into trade models. This introduction has highlighted the importance of the entry/exit decision of firms in response to changes in trade barriers. However, it is typical in many of these models to use iceberg transport costs as a general form of trade barriers that can be interchangeable with ad valorem tariffs. I show that this is not always an appropriate conclusion. Specifically, I illustrate that profit for an exporter is more elastic in response to tariffs than iceberg transport costs, which has implications for total product variety. One such implication is the possibility for there to be an anti-variety effect associated with lower transport costs while there also being a pro-variety effect associated with lower tariffs.
hdl:10197/2642
Keywords: F10; F13; F15; 330; Intra-industry trade; Trade policy; Firm heterogeneity; Monopolistic competition